Multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, preparation method thereof and sodium ion battery
By adopting multifunctional site co-doping technology in the positive electrode material of Na4Fe3 (PO4)2P2O7 of sodium ion battery, using magnesium ions and anionic groups doping, the problem of poor discharge performance of the material is solved, and higher discharge specific capacity and structural stability are achieved.
Patent Information
- Application Number
- CN202411913984.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The current sodium ion battery positive electrode material Na4Fe3(PO4)2P2O7 has poor large-scale discharge performance, mainly due to the low diffusion conductivity of sodium ion inside the material.
Through multifunctional site co-doping technology, the doping of magnesium ions and anion groups is used to enhance the crystal structure stability of the material, and improve the diffusion ability of sodium ions and the active sites of the electronic structure.
The high-power discharge capacity of the material is significantly improved. In the 2-4.0V voltage range, the discharge specific capacity at 20C current ratio reaches 67.01mAh g-1.
Smart Images

Figure CN119764384A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and mainly relates to a multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, a preparation method thereof, and a sodium ion battery. Background Art
[0002] In recent years, with the rapid growth of people's demand for electronic devices and electric travel tools, lithium-ion batteries with high specific energy, long life and high safety have been widely used in the field of energy storage and power. The resulting problems of lithium resource shortage, high cost and uneven distribution have become increasingly prominent. The abundant, easy-to-obtain and low-cost sodium resources have led to the rapid development of sodium-ion battery technology, accelerating its industrialization process in the fields of energy storage and small power.
[0003] As the positive electrode material of sodium ion batteries, the multi-iron-based polyanionic compound Na4Fe3(PO4)2P2O7 material has an open and stable structural framework, a high reversible capacity (up to 129 mAhg -1 ) and a higher average voltage (based on Fe 2+ / Fe 3 + The redox voltage is 3.2V) and is considered to be an ideal positive electrode material for the development of long-life secondary batteries. However, the intrinsic conductivity of Na4Fe3(PO4)2P2O7 materials is low, and carbon coating or carbon composite methods are generally used, mainly to build a multi-level conductive network on the surface of the material, and to enhance the electron transfer ability between particles to improve the discharge capacity of the material, but it cannot solve the problem of poor sodium ion diffusion conductivity inside the material, resulting in poor high-rate discharge performance of the material.
[0004] Therefore, there is an urgent need to develop a positive electrode material with excellent high-rate discharge performance. Summary of the invention
[0005] In order to overcome the problems in the prior art, the present invention stabilizes the crystal structure of the material, enhances the stability of the lattice, and reduces the collapse of the material caused by structural changes under high-rate discharge conditions, thereby improving the high-power discharge capacity of the material. Specifically, magnesium ion doping and multi-site doping technology for regulating anion groups are used to strengthen the crystal structure to improve the high-power discharge capacity of the material.
[0006] In an embodiment of the present invention, the present invention provides a multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, the chemical formula of the multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material is: Na [4-(3+n)y] Fe 3-x Mg x (PO4) 2-y (A) yP2O7 / C, wherein 0.001<x<0.05, 0.001<y<0.5, wherein n is the valence state of the doping anion, -2 or -4; the doping anion A is selected from SiO4 4- 、SO4 2- and CO3 2- The positive electrode material is a spherical particle with a particle size of 2 μm to 8 μm.
[0007] Based on the same inventive concept, the present invention proposes a method for preparing the above-mentioned multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, comprising the following steps:
[0008] S1. Add a carbon source, an iron source, a phosphorus source, a sodium source, a magnesium source, and an anion source into pure water according to a stoichiometric ratio, and stir to obtain slurry A;
[0009] S2, sand-grinding the slurry A to obtain slurry B;
[0010] S3, spray drying the slurry B to obtain a multifunctional site co-doped high-rate iron-based phosphate precursor powder;
[0011] S4. Sintering the multifunctional site co-doped high-rate iron-based phosphate precursor powder in stages under a protective atmosphere to obtain a multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material.
[0012] As an optional embodiment, in step S1, the carbon source is one or more of glucose, sucrose, cyclodextrin, gelatin, citric acid, ascorbic acid and starch; the iron source is ferric phosphate; the phosphorus source is one or two of diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the sodium source is one or more of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, sodium hydroxide, sodium citrate, sodium acetate and sodium oxalate; the magnesium source is magnesium acetate, magnesium oxalate or magnesium nitrate; the anion source is any one of silicon acetate, silicon oxalate, magnesium sulfate or ammonium carbonate.
[0013] As an optional embodiment, in step S1, the molar ratio of magnesium, anion group and iron in the magnesium source, anion source and iron source is 0.001-0.05:0.001-0.5:0-3.
[0014] As an optional implementation, in step S2, the sand grinding parameters are 1500-2500 rpm, the duration is 2-5 hours, and the particles are sand ground to an average particle size of 500 nm-2 μm.
[0015] As an optional embodiment, in step S3, the solid content of the slurry B is 10-35%, and during the spray drying process, the creeping speed is 25-45 rpm, the frequency is 35-60 Hz, the inlet air temperature is 200-250°C, and the outlet air temperature is 105-120°C.
[0016] As an optional implementation, in step S4, the staged calcination specifically includes:
[0017] The first stage: heating from room temperature to 300℃~380℃ at a heating rate of 1-5℃ / min, and keeping warm for 3h~10h;
[0018] The second stage: heat up to 450℃~600℃ at a heating rate of 1-5℃ / min and keep warm for 5h~12h.
[0019] Based on the same inventive concept, an embodiment of the present invention further provides a positive electrode plate, which includes a current collector and an active layer located on the surface of the current collector, and the active layer includes the above-mentioned multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material.
[0020] An embodiment of the present invention further provides a sodium ion battery, which includes the above-mentioned positive electrode plate.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The multifunctional site co-doped high-rate multi-element iron-based phosphate cathode material of the present invention adopts anion and cation co-doping, and selects magnesium ions with a radius similar to that of iron ions (slightly smaller than that of Fe) and a similar Fermi level to replace part of the iron sites of the material. Because the radius of the replaced metal ions is slightly smaller than that of Fe, the Fe-O and PO bonds in the material structure are shortened, and the Na-O bonds are elongated and easier to break, thereby increasing the diffusion coefficient of Na ions and reducing the interfacial charge transfer resistance; the anion group doping selects SiO4 with a configuration equivalent to that of the PO43- group. 4- 、SO4 2- and CO3 2- It can effectively adjust the crystal and electronic structure, increase the lattice defects in the material, increase the active sites, and increase the ionic conductivity. At the same time, it can stabilize the crystal structure of the material, enhance the stability of the lattice, and reduce the collapse of the material structure caused by structural changes under high-rate discharge conditions, thereby improving the high-power discharge capacity of the material. In the voltage range of 2-4.0V, the discharge capacity of the material at a current rate of 20C can reach 67.01mAh g -1 .
[0023] (2) The positive electrode material of the present invention adopts a pure water system and is prepared by sand milling, spray drying and a two-stage calcination method. The process is simple, the raw material source is wide, it is environmentally friendly, and it is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The SEM image and EDS surface scan image of the multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material prepared in Example 1 of the present invention, wherein Figures (a) and (b) are SEM images, and Figure (c) is an EDS spectrum of the material;
[0026] Figure 2 XRD patterns of the multinary iron-based phosphate materials prepared in Example 1 and Comparative Example 1 of the present invention, wherein (a) is the multifunctional site co-doped high-rate multinary iron-based phosphate positive electrode material prepared in Example 1, and (b) is the multinary iron-based phosphate material prepared in Comparative Example 1;
[0027] Figure 3 The multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material prepared in Example 1 of the present invention and the multi-component iron-based phosphate material prepared in Comparative Example 1 are rate curves in the voltage range of 2-4.0V and 0.2C-20C;
[0028] Figure 4 This is a SEM image of the multi-component iron-based phosphate positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0030] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] In order to improve the cycle stability and specific capacity of the positive electrode material of sodium ion battery, the inventors of this application modified the multi-element iron-based phosphate positive electrode material by doping with anion and cation multifunctional sites, doped in Fe site and PO4, and obtained a multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, whose chemical formula is: Na [4-(3+n)y] Fe 3-x Mg x (PO4) 2-y (A) y P2O7 / C, wherein 0.001<x<0.05, 0.001<y<0.5, wherein n is the valence state of the doping anion, -2 or -4; the doping anion A is selected from SiO4 4- 、SO4 2- and CO3 2- The multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material is a spherical particle with a particle size of 2 μm to 8 μm.
[0033] The method for preparing the multi-functional site doped multi-element iron-based phosphate positive electrode material comprises the following steps:
[0034] S1. Add a carbon source, an iron source, a phosphorus source, a sodium source, a magnesium source, and an anion source to pure water according to a stoichiometric ratio, and stir to obtain slurry A; wherein the carbon source is an organic carbon source, selected from one or more of glucose, sucrose, cyclodextrin, gelatin, citric acid, ascorbic acid, and starch; the iron source is preferably ferric phosphate; the phosphorus source is one or two of diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the sodium source is one or more of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, sodium hydroxide, sodium citrate, sodium acetate, and sodium oxalate; the magnesium source is any one of magnesium acetate, magnesium oxalate, and magnesium nitrate, and the anion is a soluble salt containing Si, S, and carbonate, such as one or more of ammonium salts, acetates, or oxalates, specifically any one of silicon acetate, silicon oxalate, magnesium sulfate, or ammonium carbonate. And the molar ratio of magnesium, anion groups, and iron in the magnesium source, anion source, and iron source is 0.001-0.05:0.001-0.5:0-3.
[0035] S2, sand-grind the slurry A to obtain slurry B; in this process, the sand-grinding parameters are 1500-2500rpm, the duration is 2-5h, and the average particle size of the particles is sand-grinded to 50nm-2μm. In this step, some of the raw materials are solid, and solids may be produced during the reaction, so the particle size needs to be controlled. Sand-grinding can improve the uniformity of mixing on the one hand, and provide a basis for subsequent pre-sintering and calcining on the other hand.
[0036] S3, spray drying the slurry B to obtain a multifunctional site co-doped high-rate iron-based phosphate precursor powder; in this process, the spray dryer mainly plays a role of rapid drying, and the slurry is sprayed into droplets by the spray dryer and dispersed in the hot air flow, so that the water therein evaporates quickly to obtain powder, and the entire drying process can be completed within a few seconds to tens of seconds. The process parameters of the spray dryer: the peristaltic speed is 25-45rpm, preferably 35rpm, the frequency is 35-60hz, the air inlet temperature is 200℃~250℃, preferably 220℃, the air outlet temperature is 95-120℃, preferably 105-110℃, and the specific parameters are subject to the actual operation standards of the spray dryer.
[0037] S4. The multifunctional site co-doped high-rate iron-based phosphate precursor powder is sintered in sections under a protective atmosphere to obtain a multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material. In this process, heat treatment is carried out under a protective atmosphere, wherein the protective atmosphere is one or a mixture of two or more of nitrogen, argon, and hydrogen, preferably a hydrogen-argon mixture, wherein the volume percentage of hydrogen is 5%. The heat treatment is divided into two steps: pre-sintering and secondary calcining. The pre-sintering process: the heating rate is 1 to 5°C / min, preferably 3°C / min; the temperature is 300 to 400°C, preferably 350°C, and the insulation time is 3 to 8h, preferably 5h; the secondary calcining process: the heating rate is 1 to 5°C / min, preferably 3°C / min; the temperature is 450 to 600°C, preferably 500°C, and the insulation time is 5 to 15h, preferably 10h; the cooling is furnace cooling.
[0038] The embodiment of the present application also provides a positive electrode sheet, which includes a current collector and an active layer located on the surface of the current collector, wherein the active layer includes the multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material. In addition, the above-mentioned electrode sheets can also be assembled to obtain a sodium battery with excellent performance.
[0039] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0040] Example 1
[0041] A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material and a preparation method thereof, comprising the following steps:
[0042] (1) Iron phosphate, ammonium dihydrogen phosphate, Na2C2O4, C4H6MgO4·4H2O, C8H 12O8Si and glucose are dissolved in deionized water in a molar ratio of 2.995:1.0025:2.00125:0.0005:0.0025, wherein the carbon source is added in a ratio of 2-3wt%, and the solid-liquid ratio is 3:10. The first slurry is obtained by continuous stirring at room temperature for 30 minutes.
[0043] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill to grind at 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D of the product obtained after grinding 50 The particle size is about 500nm.
[0044] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0045] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 500°C and kept at this temperature for 10 h to obtain a product with the chemical formula of Na 4.0025 Fe 2.995 Mg 0.005 (PO4) 1.9975 (SiO4) 0.0025 P2O7 / C is a magnesium-silicon anion-cation co-doped multi-iron-based phosphate positive electrode active material.
[0046] Example 2
[0047] A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material and a preparation method thereof, comprising the following steps:
[0048] (1) Iron phosphate, ammonium dihydrogen phosphate, Na2C2O4, C4H6MgO4·4H2O, C8H 12 O8Si and glucose are dissolved in deionized water in a molar ratio of 2.995:1.0025:2.00125:0.0005:0.0025, wherein the carbon source is added in a ratio of 2-3wt%, and the solid-liquid ratio is 3:10. The first slurry is obtained by continuous stirring at room temperature for 30 minutes.
[0049] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 600 nm.
[0050] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0051] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 550°C and kept for 10 h to obtain a product with the chemical formula of Na 4.0025 Fe 2.995 Mg 0.005 (PO4) 1.9975 (SiO4) 0.0025 P2O7 / C(550) magnesium-silicon anion-cation co-doped multi-component iron-based phosphate positive electrode active material.
[0052] Example 3
[0053] A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material and a preparation method thereof, comprising the following steps:
[0054] (1) Iron phosphate, ammonium dihydrogen phosphate, Na2C2O4, C4H6MgO4·4H2O, C8H 12 O8Si and glucose are dissolved in deionized water in a molar ratio of 2.95:1.025:2.0125:0.05:0.025, wherein the carbon source is added in a ratio of 2-3wt%, and the solid-liquid ratio is 3:10. The first slurry is obtained by continuous stirring at room temperature for 30 minutes.
[0055] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 500 nm.
[0056] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0057] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 500°C and kept at this temperature for 10 h to obtain a product with the chemical formula of Na 4.025 Fe 2.95 Mg 0.05 (PO4) 1.975 (SiO4) 0.025 P2O7 / C is a magnesium-silicon anion-cation co-doped multi-iron-based phosphate positive electrode active material.
[0058] Example 4
[0059] A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material and a preparation method thereof, comprising the following steps:
[0060] (1) Iron phosphate, ammonium dihydrogen phosphate, Na2C2O4, C4H6MgO4·4H2O, C8H 12O8Si and glucose were dissolved in deionized water in a molar ratio of 3:4:2:0.005:0.0025, wherein the carbon source was added in a ratio of 2-3wt%, and the solid-liquid ratio was 3:10, and stirred continuously at room temperature for 30 minutes to obtain a first slurry.
[0061] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 500 nm.
[0062] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0063] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 550°C and kept for 10 h to obtain a product with the chemical formula of Na 4.01 Mg 0.01 Fe 2.99 (PO4) 1.99 (SiO4) 0.01 P2O7 / C is a magnesium-silicon anion-cation co-doped multi-iron-based phosphate positive electrode active material.
[0064] Example 5
[0065] A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material and a preparation method thereof, comprising the following steps:
[0066] 1) Add ferric phosphate, diammonium phosphate, Na2C2O4, MgSO4 and glucose in a molar ratio of 2.99:1:1.995:
[0067] 0.01 is dissolved in deionized water, wherein the carbon source is added in a ratio of 2-3wt%, and the solid-liquid ratio is 3:10, and stirred continuously at room temperature for 30 minutes to obtain a first slurry.
[0068] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 600 nm.
[0069] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0070] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 500°C and kept at this temperature for 10 h to obtain a product with the chemical formula of Na 3.99 Fe 2.99 Mg0.01 (PO4) 1.99 (SO4) 0.01 P2O7 / C is a magnesium-sulfur anion-cation co-doped multi-component iron-based phosphate positive electrode active material.
[0071] Comparative Example 1
[0072] A method for preparing a multi-element iron-based phosphate positive electrode material comprises the following steps:
[0073] (1) Dissolve ferric phosphate, ammonium dihydrogen phosphate, and Na2C2O4 in deionized water at a molar ratio of 3:1:2, add carbon source glucose at a ratio of 2-3wt% and a solid-liquid ratio of 3:10, and stir continuously at room temperature for 30 minutes to obtain a first slurry.
[0074] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 500 nm.
[0075] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0076] (4) The obtained precursor is added into an inert atmosphere and pre-calcined at 350° C. for 5 h, and then the temperature is raised to 500° C. and kept at this temperature for 10 h, thereby obtaining a polynary iron-based phosphate positive electrode active material with a chemical formula of Na4Fe3(PO4)2P2O7 / C.
[0077] Comparative Example 2
[0078] A method for preparing a magnesium-doped multinary iron-based phosphate positive electrode material comprises the following steps:
[0079] (1) Dissolve ferric phosphate, diammonium phosphate, Na2C2O4, and C4H6MgO4·4H2O in deionized water at a molar ratio of 2.99:1.01:2:0.01, add carbon source glucose at a ratio of 2-3 wt % and a solid-liquid ratio of 3:10, and stir continuously at room temperature for 30 minutes to obtain a first slurry.
[0080] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 500 nm.
[0081] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0082] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 500°C for 10 h to obtain a product with the chemical formula of Na4Fe 2.99 Mg 0.01 (PO4)2P2O7 polybasic iron-based phosphate positive electrode active material.
[0083] Comparative Example 3
[0084] A method for preparing a silicon-doped nickel-iron-manganese-oxide-based positive electrode material comprises the following steps:
[0085] (1) Iron phosphate, diammonium phosphate, Na2C2O4, C8H 12 O8Si was dissolved in deionized water at a molar ratio of 3:4:2:0.01, and carbon source glucose was added at a ratio of 2-3wt% and a solid-liquid ratio of 3:10. The mixture was stirred continuously at room temperature for 30 minutes to obtain a first slurry.
[0086] (2) Pour the first slurry into the feed hopper of a sand mill and set the sand mill program to 1500 rpm for 1 hour, 2000 rpm for 1 hour, and 2500 rpm for 1 hour. The D50 particle size of the product obtained after grinding is about 600 nm.
[0087] (3) The slurry obtained in step 2 is subjected to spray granulation to obtain a yellow-green powder; wherein the inlet temperature of the spray granulation is 220° C., the outlet temperature is 110° C., and the peristaltic speed is 35 rpm.
[0088] (4) The obtained precursor was pre-calcined at 350°C for 5 h in an inert atmosphere, and then heated to 500°C and kept at this temperature for 10 h to obtain a product with the chemical formula of Na 4.01 Fe3(PO4) 1.99 (SiO4) 0.01 P2O7 / C is a polynary iron-based phosphate positive electrode active material.
[0089] Spectral analysis
[0090] The multi-component iron-based phosphate positive electrode material obtained in the example was subjected to SEM, EDS and XRD spectrum analysis. Taking the positive electrode materials obtained in Example 1 and Comparative Example 1 as examples, Figure 1 is the Na obtained in Example 1 4.0025 Fe 2.995 Mg 0.005 (PO4) 1.9975 (SiO4) 0.0025 SEM and EDS spectra of P2O7 / C cathode material, Figure 4 This is the SEM image of Na4Fe3(PO4)2P2O7 / C obtained in Comparative Example 1. Figure 1 From the SEM image of (a), it can be seen that the material structure is spherical particles with a particle size of about 3 μm. Figure 1(b) The EDS spectrum shows that Mg and Si are evenly distributed in the material, indicating that Mg 2+ With SiO4 4- Successfully entered the material, Figure 1 and Figure 4 The comparison shows that the surface of the undoped sample is smooth, and it is a classic hollow spherical particle obtained by spraying. The particle size is uneven, ranging from 2-10μm, while the sample doped with Mg and SiO4 4- The primary particles of the final material are obvious and the structure is more stable. Figure 2 The XRD pattern of Example 1 shows that all diffraction peaks are similar and well matched with the standard PDF card (PDF#97-023-6316). All phases can be represented by the orthorhombic system of the Pn21a space group, which indicates that a small amount of Mg, SiO4 4- The substitution does not change the crystal structure of the original NFPP (polybasic iron phosphate).
[0091] Electrical performance analysis
[0092] Battery assembly: Weigh 0.1600g of the positive electrode material prepared in the above embodiment or comparative example, add 0.0200g of conductive carbon black as a conductive agent and 0.0200g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply on aluminum foil to make a positive electrode sheet, assemble into a CR2025 button cell in a vacuum glove box with a metal sodium sheet as the negative electrode, a Whatman GF / D glass fiber separator, and an electrolyte of 1mol / L NaClO4 (EC:DMC=1:1 (volume ratio) + 5% FEC). A high rate discharge test was carried out in the range of 2-4.0V, and the results are shown in Table 1.
[0093] Table 1 Battery electrical performance test results corresponding to the positive electrode materials obtained in the examples and comparative examples
[0094]
[0095] Depend on Figure 3 As can be seen from Table 1, compared with the material prepared in Comparative Example 1, the material in Example 1 shows excellent rate advantage after 5C, indicating that co-doping with magnesium and silicon ions can stabilize the crystal structure of the material, enhance the stability of the lattice, and reduce the collapse of the material structure caused by structural changes under high-rate discharge conditions, thereby improving the high-power discharge capability of the material.
[0096] Since Mg and Si ions play different roles in stabilizing the positive electrode structure, Mg mainly occupies a specific lattice position, replaces part of the iron position, to improve the diffusion coefficient of Na ions, reduce the interface charge transfer resistance, and thus improve the structural stability of the material, while silicate ions replace part of the phosphate ions, so that the lattice defects in the material increase, the active sites become more, and the ionic conductivity increases. In contrast, the improvement effect of a single Si acid root ion doping on the diffusion dynamics of Na ions is not as significant as Mg, so the rate performance of Comparative Example 2 is worse than that of Comparative Example 3. At the same time, due to the different sites of doping of Mg and silicate ions, when the two act together, a multivariate synergistic effect is produced, which can effectively improve the structural stability of the material and reduce the phenomenon of structural collapse during charge and discharge, so the rate performance of Example 4 is significantly better than that of Comparative Example 2 and Comparative Example 3.
[0097] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A multifunctional site co-doped high-rate multi-element iron-based phosphate positive electrode material, characterized in that: The chemical formula of the multifunctional site co-doped high-rate multi-element iron-based phosphate cathode material is: Na [4-(3+n)y] Fe 3-x Mg x (PO4) 2-y (A) y P2O7 / C, wherein 0.001<x<0.05, 0.001<y<0.5, wherein n is the valence state of the doping anion, -2 or -4; the doping anion A is selected from SiO4 4- 、SO4 2- and CO3 2- One or more of .
2. The multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material according to claim 1, characterized in that: The multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material is spherical particles with a particle size of 2 μm to 8 μm.
3. The method for preparing the multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material according to any one of claims 1 and 2, characterized in that: The following steps are involved: S1. Add a carbon source, an iron source, a phosphorus source, a sodium source, a magnesium source, and an anion source into pure water according to a stoichiometric ratio, and stir to obtain slurry A; S2, sand-grinding the slurry A to obtain slurry B; S3, spray drying the slurry B to obtain a multifunctional site co-doped high-rate iron-based phosphate precursor powder; S4. Sintering the multifunctional site co-doped high-rate iron-based phosphate precursor powder in stages under a protective atmosphere to obtain a multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material.
4. The method for preparing a multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material according to claim 3, characterized in that: In step S1, the carbon source is one or more of glucose, sucrose, cyclodextrin, gelatin, citric acid, ascorbic acid and starch; the iron source is ferric phosphate; the phosphorus source is one or two of diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the sodium source is one or more of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate, sodium hydroxide, sodium citrate, sodium acetate and sodium oxalate; the magnesium source is magnesium acetate, magnesium oxalate and magnesium nitrate; the anion source is any one of silicon acetate, silicon oxalate, magnesium sulfate or ammonium carbonate.
5. The method for preparing a multifunctional site co-doped high-rate multinary iron-based phosphate positive electrode material according to claim 3, characterized in that: In step S1, the molar ratio of magnesium, anion group and iron in the magnesium source, anion source and iron source is 0.001-0.05:0.001-0.5:0-3.
6. The method for preparing a multifunctional site co-doped high-rate multinary iron-based phosphate positive electrode material according to claim 3, characterized in that: In step S2, the sand grinding parameters are 1500-2500 rpm, the duration is 2-5 hours, and the particles are sand ground to an average particle size of 500 nm-2 μm.
7. The method for preparing a multifunctional site co-doped high-rate multinary iron-based phosphate positive electrode material according to claim 3, characterized in that: In step S3, the solid content of the slurry B is 10-35%. During the spray drying process, the creeping speed is 25-45 rpm, the frequency is 35-60 Hz, the air inlet temperature is 200-250°C, and the air outlet temperature is 105-120°C.
8. The method for preparing a multifunctional site co-doped high-rate multinary iron-based phosphate positive electrode material according to claim 3, characterized in that: In step S4, the staged calcination specifically includes: Pre-calcination: heating from room temperature to 300°C-380°C at a heating rate of 1-5°C / min, and keeping warm for 3h-10h; Secondary calcination: heat to 450℃~600℃ at a heating rate of 1-5℃ / min and keep warm for 5h~12h.
9. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and an active layer located on the surface of the current collector, and the active layer includes the multifunctional site co-doped high-rate multi-component iron-based phosphate positive electrode material according to any one of claims 1 and 2.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Mixed crystal type polyanionic phosphate positive electrode material for sodium ion battery and preparation method of mixed crystal type polyanionic phosphate positive electrode material
CN113675390A
Silicate-doped iron-based polyanion positive electrode material and preparation method thereof
CN116435500A
Iron-based phosphate positive electrode active material prepared by doping iron phosphate as well as preparation method and application of iron-based phosphate positive electrode active material
CN118108201A
Doped sodium ferric phosphate sulfate positive electrode material, preparation method thereof and sodium ion battery
CN118472239A
Iron-based sodium ion full battery and preparation method therefor
WO2024011862A1
Cited By
Sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof
CN121376941A